2016
DOI: 10.1097/qai.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Route of Delivery in a Large Cohort Study of HIV-1–Infected Women—IMPAACT P1025

Abstract: Objective Investigate complications of cesarean section in a cohort of HIV-infected pregnant women. Methods IMPAACT P1025 is a prospective cohort study of HIV-1-infected women and infants, enrolled 2002 to 2013, at clinical sites in the United States and Puerto Rico. Demographic, medical, and obstetric data were collected and analyzed including cesareans indications. Delivery route was categorized as elective cesarean (ECS, before labor and <5 minutes before membrane rupture), non-elective cesarean (NECS, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…A recent American study found that 61% of WLWH planned a vaginal delivery and 27% of these ended up having a CS. A total of 24% of WLWH planning an ECS went in to labour prior to the scheduled ECS and had an EmCS performed , which corresponds to findings from our cohort, where 20.4% of WLWH planning an ECS and 32% of WLWH planning a vaginal delivery ended up having an EmCS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A recent American study found that 61% of WLWH planned a vaginal delivery and 27% of these ended up having a CS. A total of 24% of WLWH planning an ECS went in to labour prior to the scheduled ECS and had an EmCS performed , which corresponds to findings from our cohort, where 20.4% of WLWH planning an ECS and 32% of WLWH planning a vaginal delivery ended up having an EmCS.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with the decreasing rate of ECS, Livingston et al . reported only 39% of American WLWH planning an ECS . The primary indications of CS were prior CS (33%) and PMTCT (26%).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of women fulfilling the virological criteria for vaginal delivery in Finland is comparable to that reported from France, Denmark and the US [ 13 , 17 , 20 ]. However, whilst over 75% of women fulfilling these criteria in Finland deliver vaginally, only half of them in France or the US do so [ 13 , 17 ]. This rate was not reported in the Danish study [ 20 ].…”
Section: Discussionsupporting
confidence: 71%
“…The transition from CS to vaginal delivery in clinical practice has been slow; 40–66% of women living with HIV (WLWH) in Europe, Canada and the US still deliver by CS and 22–51% by elective CS despite excellent virological treatment results [ 4 , 12 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study collected detailed information during pregnancy, allowing careful control for potential confounders. However, the study followed infants only for 1 year and reduced infant follow-up to 6 months in 2007; as a result, this study has primarily focused on adverse birth and early neonatal outcomes [56]. The Pediatric AIDS Clinical Trials Group (PACTG) 219/219C study followed 3552 infected children (90% perinatally-acquired) and 2342 HEU youth for long-term outcomes, including neurodevelopment and neurological functioning, congenital anomalies, growth, cancer and mitochondrial dysfunction [5760].…”
Section: Art Safety Surveillance Programsmentioning
confidence: 99%